Patient and health system delays among tuberculosis patients attending DOTS centres of Kamrup (metro) district, Assam - Gope, Abhishek; Baruah, Kanika K.; Ojah, Jutika; Baruah, Rupali (International Journal Of Community Medicine And Public Health, 2017)
Background: Among the North eastern states, Assam has the highest burden of tuberculosis. Early diagnosis and prompt treatment is essential for effective control of tuberculosis. Methods: A cross sectional study was conducted among new smear positive tuberculosis cases above 15 years in Kamrup (Metrolpolitan) district of Assam from August 2015 to July 2016. Results: The mean patient delay was 34.2 days and the mean health system delay was 30.34 days. Female gender and patients who made first contact with non-formal health care providers were significantly associated with patient delay while illiteracy and age more than 35 years had significant association with health system delay. Conclusions: Median patient delay was found to be more than median health system delay. As patient delay was significantly associated with non-formal health care providers, the study proposes integration of non-formal health care providers with RNTCP which can reduce the patient delay.